Development of a Cable-Driven Robot with a Compensation Measurement System for Bimanual and Cognitive Rehabilitation of Stroke - Alves, Thiago; Gonçalves, Rogério S. (Anais Estendidos do Simpósio Brasileiro de Robótica e Simpósio Latino-Americano de Robótica (SBR/LARS), 2024)
Stroke remains the leading cause of disability, causing significant motor and cognitive deficits such as function and memory loss. Recovery is based on neuroplasticity; wherein undamaged brain areas assume the functions of damaged regions. Bimanual robotic devices stimulate hemispheric activation and enhances neuroplasticity and recovery. This thesis introduced a cable-driven robot and serious games for bimanual and cognitive rehabilitation. A system was developed to measure compensation and distinguish motor recovery from postural adjustments. Two stroke groups underwent bimanual or cognitive exercises with serious games, leading to significant improvements (p <0.05) in several parameters and clinical scales (Fugl-Meyer and Motor Activity Log).